Effect of Productive Asset Quality and Problem Credits on Banking Profitability - Elyas Akbar (BJRM (Bongaya Journal of Research in Management), 2021)
This study aims to partially analyze and examine the effect of the quality of earning assets and non-performing loans on bank profitability. This study uses secondary data obtained from the financial statements of PT Bank Negara Indonesia Tbk. Makassar Regional Office for the period 2011 - 2019 using the cross-sectional technique. This study used 36 samples. Furthermore, it will be tested with several testing stages, such as the classic assumption test in normality, multicollinearity, and autocorrelation—methods of data analysis using multiple linear regression analysis techniques. This study indicates that partially the quality of earning assets has a positive and significant effect on profitability. In contrast, non-performing loans have no positive and significant effect on profitability. Simultaneously, productive asset quality and non-performing loans affect profitability.